(untitled) (Itinera, 2021)
Sensible qualities, not presumed abstract or pure aesthetic properties, are the main source for the Diderot’s and Reid’s aesthetic theories. Both authors work on the perceptual activity in normal situations and in blind people’s cognitive experience. This essay is aimed at emphasizing both the connections between perceptual activity and aesthetic experience and the role of aesthetic devices in the cognitive life. In Diderot sensible qualities are connected to emotions; in Reid they are the natural signs of emotions and mental properties. This kind of relationship is the key to interpreting how cognitive activity is configured as an aesthetic experience because of the sensible qualities’ role.